REDESAIN PASAR SENEN BLOK 3 DENGAN PENDEKATAN ARSITEKTUR TROPIS - Junaedi, Fadil Hakim (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
Traditional markets which used to be the center of trade and the community's economy have been slightly displaced by the existence of modern markets, especially in big cities. Most traditional markets in Indonesia are not well organized so that residents cannot shop at the market comfortably. This is caused by the market structure being less organized and its cleanliness not being well maintained. Pasar Senen Blok 3, as one of the traditional markets in a particular area, has an important role in the economic and social ecosystem of society. There are problems at Senen Market, such as the arrangement of trading spaces, inadequate facilities, and minimal ventilation and natural lighting. Based on these problems, a redesign of Pasar Senen Block 3 will be carried out using a Tropical Architectural Approach. According to Lippsmeier, Tropical Architecture is a building design designed to solve problems found in tropical areas, which has principles such as thermal comfort, air circulation, natural application, and reducing solar radiation. Therefore, the Tropical Architectural Approach to the Redesign of Senen Block 3 Market is one of the efforts to develop and manage the Traditional Market.